Rationally Designed Variants of α-Synuclein Illuminate Its in vivo Structural Properties in Health and Disease - Dettmer, Ulf (Frontiers in Neuroscience, 2018)
α-Synuclein (αS) is a conserved and abundant neuronal protein with unusual structural properties. It appears to partition between folded and unstructured states as well as between membrane-bound and aqueously soluble states. In addition, a switch between monomeric and tetrameric/multimeric states has been observed recently. The precise composition, localization and abundance of the multimeric species are under study and remain unsettled. Yet to interfere with disease pathogenesis, we must dissect how small changes in αS homeostasis may give rise to Parkinson’s disease (PD), dementia with Lewy bodies (DLB) and other human synucleinopathies. Rationally-designed αS point mutations that prevent the protein from populating all states within its normal folding repertoire have continued to be instrumental in bringing new insights into its biochemistry in vivo. This review summarizes biochemical and cell biological findings about αS homeostasis from different labs, with a special emphasis on intact-cell approaches that may preserve the complex, metastable native states of αS.